Modification of YEM broth for medium scale production of legume inoculants - Ormeño-Orrillo, Ernesto (1998)
Yeast-extract-mannitol (YEM) broth, a widely used laboratory medium for the cultivation of rhizobia, was modified to reduce its cost and made it suitable for medium scale production of rhizobial legume inoculants. Yeast extract and mannitol, the most expensive ingredients, were reduced or substituted with more cheap substrates. With the addition of 1,1 g/L of glutamic acid or food grade sodium glutamate, yeast extract can be reduced to 0,05 g/L without affecting growth. Mannitol can be replaced with 12,5 g/L of pharmaceutical grade glycerin for Bradyrhizobium strains or with 10 g/L of food grade sugar for Rhizobium strains. The symbiotic properties of rhizobia grown on modified media were not affected.